Regulating fintech for sustainable development in the People's Republic of China - Zhong Xu; Ruihui Xu (Asian Development Bank Institute (ADBI), 2019)
The rapid rise of financial technology (fintech) in the People's Republic of China (PRC) inevitably generates financial risks. To prevent and resolve these risks, the government has regulated many fintech application areas, including peer-to-peer lending, third-party payment, cryptocurrency, etc. Additional measures such as financial standardization, infrastructure, and investor protection have also been strengthened to promote sustainable fintech development. The PRC is striking a balance between encouraging fintech innovation and reinforcing regulation. This study reviews both the PRC's regulations and supportive approaches.
Keywords: G2; G15; O16; 330; financial technology; fintech